Measuring the dark triad: a meta-analytical SEM study of two prominent short scales - Knitter, Lukas A.; Hoffmann, Jerome; Eid, Michael; Koch, Tobias (Frontiers in Psychology, 2025)
This research examines the factor structure and psychometric properties of two well-known Dark Triad personality trait questionnaires: the Short Dark Triad (SD3) and the Dirty Dozen (DD). By analyzing data from 11 (SD3) and 5 (DD) carefully selected studies in the United States and Canada, this meta-analysis uncovers unexpected correlations among questionnaire items, challenging existing assumptions. The study employs a two-stage structural equation modeling approach to evaluate various measurement models. Conventional models, such as the correlated factor and orthogonal bifactor models, fail to explain the irregular correlations. For Dirty Dozen items, a bifactor-(S·I-1) model is more suitable than the orthogonal bifactor model, significantly affecting interpretation. On the other hand, the complex structure of the SD3 necessitates item revision to enhance reliability, discriminant validity, and predictive validity. These findings emphasize the need for refining and clarifying concepts in item revision. Furthermore, the research highlights the overlap between Machiavellianism and psychopathy, particularly in relation to revenge-related items, suggesting the need for differentiation between these traits or the identification of distinct core characteristics.